Chinese Perspectives on the Environment and Sustainable Development. - Ye, Wenhu (Issues in contemporary Chinese thought and culture, 2013)
The authors examine the status quo, as well as the challenges of and possible solutions of China's environment problems. It provides us with the most authoritative points of view on environmental protection and sustainable development in China.